Inovasi Produk Kue Kering Sebagai Camilan Sehat dengan Penambahan Daun Sirih Cina - Sayid Agil Jenar Sakti; I. F Romadhoni; Niken Purwidiani; Andika Kuncoro Widagdo (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study was to determine the effect of the addition of Chinese betel leaves on the organoleptic properties of aroma, taste, colour, texture of kastengel cookies, and the nutritional content of kastengel cookies with the addition of Chinese betel leaves. This type of research is an experiment, this research is looking for the best recipe for kastengel with the addition of Chinese betel leaves. The data collection technique used was observation which involved 30 panellists, who were assisted by using a panellist sheet with a score of 1-5. In this study using quantitative methods that use numbers in data collection and analysis of measurable data, the data analysis technique used is AnavaTunggal (Analysis of varience) with the help of the SPSS version 29 program, if the results use a real effect test, then the next test uses the Duncan test to determine significant differences. The results showed that there was an effect of differences in aroma, colour, and taste on kastengel products, but could not affect the texture. This study proves that Chinese betel leaves not only add a unique aroma and flavour to pastries, but also contribute various health benefits thanks to the content of active compounds such as antioxidants. Organoleptic tests involving a number of panelists showed that the product was well received in terms of taste, colour and aroma. In addition, nutritional analysis revealed an increased antioxidant content in kastengel cookies enriched with Chinese betel leaves, making them a healthier snack option compared to conventional products.